Increased cardiac macrophages in Sorbs2-deficient hearts: revealing a potential role for macrophage in responding to embryonic myocardial abnormalities - Hu, Beibei; Liu, Xiangyang; Xiong, Shanshan; Gong, Qin; Yang, Junjie; Shi, Hongjun; Zhang, Min; Liang, Fei; Zhang, Zhen (Frontiers in Genetics, 2025)
Macrophages are known to support cardiac development and homeostasis, contributing to tissue remodeling and repair in the adult heart. However, it remains unclear whether embryonic macrophages also respond to abnormalities in the developing heart. Previously, we reported that the structural protein Sorbs2 promotes the development of the second heart field, with its deficiency resulting in atrial septal defects (ASD). In analyzing RNA-seq data, we noted an upregulation of macrophage-related genes in Sorbs2−/− hearts. Immunostaining and lineage-tracing confirmed an increase in macrophage numbers, underscoring a macrophage response to myocardial abnormalities. Partial depletion of macrophages led to downregulation of genes involved in lipid metabolism, muscle development and organ regeneration, alongside upregulation of genes associated with DNA damage-induced senescence and cardiomyopathy. Additionally, a non-significant increase in septal defects in macrophage-depleted Sorbs2−/− hearts suggests a potential reparative function for macrophages in maintaining structural integrity. Valve formation, however, remained unaffected. Our findings suggest that embryonic macrophages might sense abnormalities in embryonic cardiomyocytes and could adaptively support cardiac structure and function development in response to myocardial abnormalities.